Revitalisasi Pendidikan Vokasi Melalui Edupreneurship: Mendorong Kemandirian Ekonomi Siswa SMK di Era Society 5.0 - Nisa, Nur Harini Khoirun; Fatmawati, Sri; Nizar, M. Samsul; Marwanto, Marwanto; Kuat, Tri (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the revitalization of vocational education through edupreneurship in promoting the economic independence of vocational high school students in the era of society 5.0. This study uses a descriptive qualitative approach. The research subjects were selected using purposive sampling techniques, with criteria for vocational high schools that have integrated the edupreneurship program into their learning processes. Data collection techniques were carried out through semi-structured interviews, observations, and documentation studies. The analysis process was conducted through data reduction stages, data presentation, and conclusion drawing. The results of the analysis show that vocational education, particularly in vocational high schools (SMK), plays a strategic role in producing a generation that is job-ready while also capable of creating jobs independently. However, various structural and cultural challenges such as competency mismatch, weak technology integration, and low entrepreneurial spirit remain major obstacles in achieving the economic independence of graduates. In the era of Society 5.0, which demands technological proficiency and sustainable innovation, a more adaptive and transformative educational approach is needed. In this context, edupreneurship emerges as a strategic solution to revitalize vocational education to make it more contextual, productive, and highly competitive.